Dedicated to Forming the Legal Culture of Future Customs Service Bodies' Employees Modern Requirements - Ravshanovna, Rafikova Muattar (Research Parks Publishing LLC, 2023)
The article describes the modern requirements for the formation of the legal culture of the employees of the future customs service.